Development And Characterization Of Technetium-99m Radiolabeled Nanoparticles - Aziz, Amir Firdaus Abdul (2023)
Introduction: The appealing physical properties of technetium-99m (99mTc), have made it a commonly utilized radionuclide for SPECT imaging. In the field of nuclear medicine, the high potential of nanoparticles as a diagnostic agent when radiolabeled with 99mTc has attracted the attention of many researchers. This study aims to develop and characterize 99mTc-radiolabeled nanoparticles from chitosan and beta-cyclodextrin (β-CD). Methods: Chitosan nanoparticles were prepared using the ionotropic gelation method, and the effects of several parameters on the particle size and stability of the formed nanoparticles were evaluated. The optimized nanoparticles were then radiolabeled with 99mTc, and the stability of the complex was evaluated. The suitability of β-CD nanoparticles for radiolabeling with 99mTc was also evaluated and characterized accordingly. Results: The optimal concentration of chitosan and the pH for producing chitosan nanoparticles was 0.5 mg/ml and pH 4.6, respectively, and the smallest particle size obtained was 81 ±6.7 nm with a narrow size distribution (PDI = 26 ±0.4 %). The particles showed good stability for at least 5 months. β-CD nanoparticles on the other hand, has a particle size of 692 ±40.7 nm, and the particle size remains stable for one day. The produced nanoparticles were then radiolabeled with 99mTc, with an activity range of 100–111 MBq (2.7–3 mCi). The labelling efficiency recorded was more than 90%, with a radiolabeling stability of 2 hours for β-CD and more than 6 hours for chitosan nanoparticles. Conclusions: Based on the findings, it is possible to conclude that both chitosan and β-CD nanoparticles are suitable for radiolabeling with 99mTc.